2022
DOI: 10.3389/fmars.2022.985496
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the coral microbiome at the scale of tissue-specific habitats within the coral meta-organism

Abstract: As sequencing techniques have advanced and become cheaper in recent years, there has been a rapid increase in the number of studies conducted into the role of the microbiome in coral health, physiology, and response to environmental change. However, there is substantial variation in the methodological approaches applied. For example, DNA extraction protocols and the types of tissues sampled from the coral meta-organism are known to influence the downstream analyses of the amplified microbial communities and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…Corals harbor a dynamic microbiota featuring a wide variety of taxa consisting of viruses and members of the Archaea, Eukarya, and Eubacteria domains [6,7]. Within this microbial assemblage are bacteria that can inhabit different niches within the coral, i.e., the mucopolysaccharide surface layer, skeleton, and tissues [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Corals harbor a dynamic microbiota featuring a wide variety of taxa consisting of viruses and members of the Archaea, Eukarya, and Eubacteria domains [6,7]. Within this microbial assemblage are bacteria that can inhabit different niches within the coral, i.e., the mucopolysaccharide surface layer, skeleton, and tissues [8,9].…”
Section: Introductionmentioning
confidence: 99%
“… Ricci et al. (2022) found a high abundance of Pseudoalteromonas species in the tissues and skeleton of Pocilloporidae from the GBR that was not observed in the present study, possibly due to different bacterial communities associated with different sample collection methods targeting different regions of the holobiont ( Bergman et al. 2022 ) or potentially seasonal difference in the microbiome which need to be assessed in future studies ( Sharp et al.…”
Section: Discussionmentioning
confidence: 54%
“…Tissues can also be dissected from the skeleton with a scalpel or razor blade, although the skeleton would almost certainly be present in any sample using this method ( Littman et al, 2010 ; Kvennefors et al, 2012 ; Sudek et al, 2012 ). Another means to acquire exclusively tissue would be to add preservative and/or fixative that would allow downstream DNA extraction and then decalcify the coral using salt buffers or a mixture of formic acid and sodium nitrate ( Berzins et al, 2011 ; Hernandez-Agreda et al, 2018a ; Bergman et al, 2022 ). Tissue samples can be stored in ultra-freezers, in 100% molecular grade ethanol, or depending on the subsequent microbiological analysis, it can be fixed with 4% paraformaldehyde at 4°C for 12 h ( Staley et al, 2017 ; Hernandez-Agreda et al, 2018a ).…”
Section: Best Practices and Options In Methods For Assessment Of Cora...mentioning
confidence: 99%
“…These studies suggest that no specific DNA extraction kit must be used with coral samples (as exists for soils and plants studies). Bergman et al (2022) also compared the output of microbial community analysis from 2 different coral species with 3 different kits (see citation for details) and found that, at least for the same coral species, each kit resulted in similar alpha and beta diversity estimates. Given these data, we recommend that research be carried out on the lysis and methods that each DNA extraction kit uses to determine the most suitable kit for a given sample type.…”
Section: Best Practices and Options In Methods For Assessment Of Cora...mentioning
confidence: 99%